International Liberal Movement and the European Integration Processes. Program and Organization Evolution Alliance of Liberals and Democrats for Europe – ALDE (Economic and Political Thought, 2013)
Liberals exerted considerable influence on the European integration. Bothpoliticians associated with liberalism and liberal organizations interested inthe integration of the continent had that impact. There was a feedback: variousinterwar ideas of uniting the continent were important for liberal programsand attempts to develop Trans-European dialogue between political parties.The article deals with international liberal movement that was involved in theEuropean policy from the very beginning of its existence. From the late 40sLiberal International issued documents that confirmed liberals’ influence onthe integration of the continent. Liberals paid attention to democratization ofthe Union, European institutions and citizens’ participation in the decision--making process. The importance of liberal policy was also indicated by theparticipation of freedom parties in member states’ governments, in whichthey held key ministerial positions in spite of unstable election results.